‘Pre-Islamic Survivals’ in Muslim Central Asia - Weller, R. Charles. author. (orcid)0000-0001-6585-9500 Link aut Link
XIX, 405 p. 1 illus.
Keywords: The book traces the conceptual lens of historical-cultural ‘survivals’ from the late 19th-century theories of E.B. Tylor, James Frazer, and others, in debate with monotheistic ‘degenerationists’ and Protestant anti-Catholic polemicists, back to its origins in Jewish, Christian and Muslim traditions as well as later more secularized forms in the German Enlightenment and Romanticist movements. These historical sources, particularly the ‘dual faith’ tradition of Russian Orthodoxy, significantly shaped both Tsarist and later Soviet ethnography of Muslim Central Asia, helping guide and justify their respective religious missionary, social-legal, political and other imperial agendas. They continue impacting post-Soviet historiography in complex and debated ways. Drawing from European, Central Asian, Middle Eastern and world history, the fields of ethnography and anthropology, as well as Christian and Islamic studies, the volume contributes to scholarship on ‘syncretism’ and ‘conversion’, definitions of Islam, history as identity and heritage, and more. It is situated within a broader global historical frame, addressing debates over ‘pre-Islamic Survivals’ among Turkish and Iranian as well as Egyptian, North African Berber, Black African and South Asian Muslim Peoples while critiquing the legacy of the Geertzian ‘cultural turn’ within Western post-colonialist scholarship in relation to diverging trends of historiography in the post-World War Two era. R. Charles Weller, Associate Professor of History (Career), Washington State University, and Senior Research Fellow, Department of Religion and Culture, Al-Farabi Kazakh National University, Almaty, Kazakhstan.